1973
DOI: 10.1139/x73-075
|View full text |Cite
|
Sign up to set email alerts
|

Sugar-maple Borer Injury in Four Hardwood Stands in New Hampshire

Abstract: Forty-three percent of 348 sugar-maple trees, Acersaccharum Marsh., in 60 plots, in four hardwood stands were injured by the sugar-maple borer, Glycobiusspeciosus (Say). The percentage of injured trees was greater in uneven-aged stands than in even-aged stands. The microorganisms isolated from discolored and decayed wood associated with borer injuries were the same as those isolated from discolored and decayed wood associated with wounds on sugar maple.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Forest edges and open stands might be preferred habitat for Cerambicidae because of increased light levels (Barbalat 1996). However, Shigo et al (1973) found little difference in percentage of trees attacked by G. speciosus between cut and uncut stands. Some species of wood-borers have greater reproductive success when ovipostion occurs on stressed or damaged trees (Rose and Lindquist 1997).…”
Section: Wood-boring Insectsmentioning
confidence: 65%
See 3 more Smart Citations
“…Forest edges and open stands might be preferred habitat for Cerambicidae because of increased light levels (Barbalat 1996). However, Shigo et al (1973) found little difference in percentage of trees attacked by G. speciosus between cut and uncut stands. Some species of wood-borers have greater reproductive success when ovipostion occurs on stressed or damaged trees (Rose and Lindquist 1997).…”
Section: Wood-boring Insectsmentioning
confidence: 65%
“…Damaged or stressed trees in open or thinned forests serve as ideal oviposition sites for the maple borer. Shigo et al (1973) and Hopkin and Howse (1998) found more borer damage along roadsides than within forest stands. Newton and Allen (1982) suggest that topographical or site characteristics play a role in the spatial distribution of attacked trees.…”
Section: Wood-boring Insectsmentioning
confidence: 93%
See 2 more Smart Citations
“…If I did not at first find scars, I continued to survey until I had exhausted the likelihood of a false negative, usually examining well over 100 mature sugar maple trees during a period of more than an hour. Given that the beetle attacks approximately a third of the maples present in forests where the beetle occurs [10,15], finding this many unaffected trees sequentially when the beetle has been present is extremely unlikely [9]. Surveying both sides of the predicted boundary in new locations, even with a small number of sites, is a strong test of the model [16].…”
Section: Predicting and Validating The New Geographical Rangementioning
confidence: 99%